2014
DOI: 10.1111/aos.12427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and viral load of oncogenic human papillomavirus (HPV) in pterygia in multi‐ethnic patients in the Malay Peninsula

Abstract: ABSTRACT.Purpose: The aim of the study was to determine the prevalence of human papillomavirus (HPV) in primary and recurrent pterygia samples collected from different ethnic groups in the equatorial Malay Peninsula. Methods: DNA was extracted from 45 specimens of freshly obtained primary and recurrent pterygia from patients and from 11 normal conjunctival swabs from volunteers with no ocular surface lesion as control. The presence of HPV DNA was detected by nested PCR. PCR-positive samples were subjected to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
(60 reference statements)
2
13
0
1
Order By: Relevance
“…According to these reviews, the lowest prevalence of HPV in pterygium samples has been identified in Turkish, Japanese, and Ecuadoran patients (0%, 4.8%, and 21%, respectively), [82][83][84] while the highest prevalence has been reported for Italian, Brazilian, and English patients (100%, 58.3%, and 50%, respectively). [84][85][86] Recent research also reports contrasting results: Chong et al 87 found a prevalence of 64.4% in patients from the Malay Peninsula, whereas Woods 88 reported 0% in patients from Australia. The disparity in these prevalence rates has been attributed to ethnic and geographical factors, as well as to the laboratory techniques and study designs used.…”
Section: Viral Infections and Hereditymentioning
confidence: 98%
“…According to these reviews, the lowest prevalence of HPV in pterygium samples has been identified in Turkish, Japanese, and Ecuadoran patients (0%, 4.8%, and 21%, respectively), [82][83][84] while the highest prevalence has been reported for Italian, Brazilian, and English patients (100%, 58.3%, and 50%, respectively). [84][85][86] Recent research also reports contrasting results: Chong et al 87 found a prevalence of 64.4% in patients from the Malay Peninsula, whereas Woods 88 reported 0% in patients from Australia. The disparity in these prevalence rates has been attributed to ethnic and geographical factors, as well as to the laboratory techniques and study designs used.…”
Section: Viral Infections and Hereditymentioning
confidence: 98%
“…17 Epidemiologic studies suggest that exposure to ultraviolet B light (UVB) is an important risk factor. 1,14,[18][19][20][21][22][23] In particular, pterygia are more common in individuals who live near the equator and in those who work outdoors. UVB has been postulated to interact with a variety of cofactors, including HPV and the p53 tumor suppressor gene, to genetically alter nasal limbal epithelial stem cells, leading to the development or recurrence of pterygia.…”
Section: Pterygiummentioning
confidence: 99%
“…UVB has been postulated to interact with a variety of cofactors, including HPV and the p53 tumor suppressor gene, to genetically alter nasal limbal epithelial stem cells, leading to the development or recurrence of pterygia. 1,14,18,19,24 This ''two-hit'' hypothesis is supported by the detection of the high-risk HPV strains 16 and 18, encoding E6 and E7 proteins, which interfere with p53 function, in pterygium. 14,22,24,25 However, the rates of detection of HPV in pterygia vary considerably (range, 0%-100%) in published reports.…”
Section: Pterygiummentioning
confidence: 99%
See 1 more Smart Citation
“…El potencial oncogénico del VPH ha sido ampliamente estudiado. El ADN viral se encuentra en tumores benignos y malignos, papilomas especialmente de las mucosas: VPH 16 y VPH 18 (11)(12)(13)(14).…”
Section: Fisiopatologíaunclassified